An in vitro study on anti-carcinogenic effect of remdesivir in human ovarian cancer cells via generation of reactive oxygen species. (31st March 2022) - Lee, Chang Min; Kang, Mi-Ae; Bae, Jun Sang; Park, Kyungmoon; Yang, Yung-Hun; Lee, Jongsung; Jang, Kyu Yun; Park, See-Hyoung
Background: Remdesivir is an anti-viral drug that inhibits RNA polymerase. In 2020, remdesivir was recognized as the most promising therapeutic agents against coronavirus disease 2019 (COVID-19). However, the effects of remdesivir on cancers have hardly been studied. Purpose: Here, we reported that the anti-carcinogenic effect of remdesivir on SKOV3 cells, one of human ovarian cancer cell lines. Research design: We anlalyzed the anti-carcarcinogenic effect of remdesivir in SKOV3 cells by performing in vitro cell assay and western blotting. Results: WST-1 showed that remdesivir decreased cell viability in SKOV3 cells. Experiments conducted by Muse Cell Analyzer showed that remdesivir-induced apoptosis in SKOV3 cells. We found that the expression level of FOXO3, Bax, and Bim increased, whereas Bcl-2, caspase-3, and caspase-7 decreased by remdesivir in SKOV3 cells. Furthermore, we observed that intracellular reactive oxygen species (ROS) level increased after treatment of remdesivir in SKOV3 cells. Interestingly, cytotoxicity of remdesivir decreased after treatment of N-Acetylcysteine. Conclusion: Taken together, our results demonstrated that remdesivir has an anti-carcinogenic effect on SKOV3 cells vis up-regulation of reactive oxygen species, which suggests that remdesivir could be a promising reagent for treatment of ovarian cancer.